DETERMINAN KESADARAN WAKAF: ALTRUISME, LITERASI, KEPERCAYAAN, DAN RELIGIUSITAS - Al Anshari; Siti Jamilah (Media Riset Bisnis Manajemen Akuntansi, 2026)
Waqf is a key Islamic philanthropy instrument for socio-economic empowerment, yet its realization remains far below its potential. This study examines how altruism (X1), waqf literacy (X2), and trust (X3) affect waqf awareness (Y), with religiosity (Z) as a mediating variable. A quantitative survey was administered online to 147 Muslim respondents in Indonesia using a 5-point Likert scale. Data were analyzed with SEM-PLS (SmartPLS) through measurement-model evaluation (outer loadings, reliability, AVE) and structural-model testing (R², bootstrapping).The model explains 73.8% of the variance in religiosity (R²=0.738) and 76.8% in waqf awareness (R²=0.768). Altruism significantly increases religiosity (β=0.575; p0.001) and waqf awareness directly (β=0.218; p=0.002), and also indirectly via religiosity (β=0.275; p0.001). Waqf literacy has a significant direct effect on waqf awareness (β=0.245; p=0.001), but its effect on religiosity is not significant (β=0.116; p=0.068), resulting in a non-significant mediation path (β=0.055; p=0.092). Trust significantly strengthens religiosity (β=0.284; p0.001) but shows no direct effect on waqf awareness (β=0.032; p=0.658); its influence emerges through full mediation of religiosity (β=0.136; p0.001). Religiosity is a strong determinant of waqf awareness (β=0.478; p0.001). These findings imply that strengthening religious-based framing, improving waqf literacy, and enhancing institutional credibility are critical to increasing waqf awareness.Keywords: altruism; religiosity; trust; waqf awareness; waqf literacy